2017
DOI: 10.1038/nmeth.4294
|View full text |Cite|
|
Sign up to set email alerts
|

Nm-seq maps 2′-O-methylation sites in human mRNA with base precision

Abstract: The ribose of RNA nucleotides can be 2′-O-methylated (Nm). Despite advances in high-throughput detection, the inert chemical nature of Nm still limits sensitivity and precludes mapping in mRNA. We leveraged the differential reactivity of 2′-O-methylated and 2′-hydroxylated nucleosides to periodate oxidation to develop Nm-seq, a sensitive method for transcriptome-wide mapping of Nm with base precision. Nm-seq uncovered thousands of Nm sites in human mRNA with features suggesting functional roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
258
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(265 citation statements)
references
References 37 publications
7
258
0
Order By: Relevance
“…Nm-seq uncovered over 7,000 potential methylation sites in human mRNA revealing a consensus sequence and enrichment within three amino acid codons and extensive ribose methylation in all four bases. The same approach has been used to map these sites in rRNA (Dai et al, 2017; Zhu et al, 2017). …”
Section: Ribose Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nm-seq uncovered over 7,000 potential methylation sites in human mRNA revealing a consensus sequence and enrichment within three amino acid codons and extensive ribose methylation in all four bases. The same approach has been used to map these sites in rRNA (Dai et al, 2017; Zhu et al, 2017). …”
Section: Ribose Modificationmentioning
confidence: 99%
“…In vivo , 2’-OMe is typically found in unstructured CDS regions of mRNA, with half of all sites falling within 50 nucleotides of the nearest splice site, suggesting a link between structural elements and mRNA processing outcomes. Interestingly, 2’-OMe sites concentrate to six codons that encode three amino acids: glutamate, lysine, and glutamine, perhaps dependent on the RNA-binding properties of specific methyltransferase (Dai et al, 2017). This suggests that 2’-OMe in mRNA may affect translation efficiency, a concept that has been demonstrated in modified bacterial mRNA (Hoernes et al, 2016).…”
Section: Properties Of Mrna Modifications – Structure and Functionmentioning
confidence: 99%
“…The m 6 A-mapping concept was quickly applied to other modified nucleotides, resulting in transcriptome-wide maps of N 6 ,2 0 -O-dimethyladenosine (m 6 A m ) [10], 5-methylcytidine (m 5 C) [11][12][13], pseudouridine [14][15][16], 5-hydroxymethylcytidine (hm 5 C) [17], 2 0 -O-methylated nucleotides (N m ) [18], and N 1 -methyladenosine (m 1 A) [19,20]. The m 6 A-mapping concept was quickly applied to other modified nucleotides, resulting in transcriptome-wide maps of N 6 ,2 0 -O-dimethyladenosine (m 6 A m ) [10], 5-methylcytidine (m 5 C) [11][12][13], pseudouridine [14][15][16], 5-hydroxymethylcytidine (hm 5 C) [17], 2 0 -O-methylated nucleotides (N m ) [18], and N 1 -methyladenosine (m 1 A) [19,20].…”
Section: Epitranscriptomic Regulation Of Mrnamentioning
confidence: 99%
“…Although m 6 A and pseudouridine are well-documented epi transcriptomic modifications, and their mapping can be performed reliably 10,11 , the validity of newer modification maps is unclear, because the modifications were mapped from sequencing data but not biochemically validated. A recent study 12 of the mammalian transcriptome mapped approximately 3,500 nucleotides that contain methyl groups on the ribose part of the molecules. However, subsequent reanalysis showed that the key sequence motifs discovered in this study matched those of 'primer' sequences used to generate complementary DNA, a common sequencing artefact 13 .…”
Section: Years Agomentioning
confidence: 99%